2019
DOI: 10.1093/mnras/stz1728
|View full text |Cite
|
Sign up to set email alerts
|

Powerful AGN jets and unbalanced cooling in the hot atmosphere of IC 4296

Abstract: We present new Karl G. Jansky Very Large Array (VLA, 1.5 GHz) radio data for the giant elliptical galaxy IC 4296, supported by archival radio, X-ray (Chandra, XMM-Newton) and optical (SOAR, HST) observations. The galaxy hosts powerful radio jets piercing through the inner hot X-ray emitting atmosphere, depositing most of the energy into the ambient intra-cluster medium (ICM). Whereas the radio surface brightness of the A configuration image is consistent with a Fanaroff-Riley Class I (FR I) system, the D confi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 65 publications
6
26
0
Order By: Relevance
“…This scenario looks very similar to some galaxy clusters, that are shown to host giant cavities, with lobes extending over the cooling region (e.g., Gitti et al, 2007). Some analyses of singular groups already suggested that jets extending well over the core could violate the standard AGN feeding-feedback model (e.g., O'Sullivan et al, 2011;Grossová et al, 2019). However, this is the first work to prove that a significant fraction of the galaxy groups population effectively shows hints that support this scenario.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…This scenario looks very similar to some galaxy clusters, that are shown to host giant cavities, with lobes extending over the cooling region (e.g., Gitti et al, 2007). Some analyses of singular groups already suggested that jets extending well over the core could violate the standard AGN feeding-feedback model (e.g., O'Sullivan et al, 2011;Grossová et al, 2019). However, this is the first work to prove that a significant fraction of the galaxy groups population effectively shows hints that support this scenario.…”
Section: Discussionsupporting
confidence: 66%
“…We then argue that the biggest radio galaxies are found in the centre of galaxy groups. This was already hinted by multiple works on giant radio galaxies (e.g., Mack et al 1998;Machalski et al 2004;Subrahmanyan et al 2008;Chen et al 2012;Grossová et al 2019;Cantwell et al 2020, and references therein). However, this is the first time that they are included as sources in a large sample of groups, and their link to the environment is studied with respect to "classical" radio sources.…”
Section: Discussionmentioning
confidence: 78%
“…Our indexes are consistent (1-1.5σ) with those from Best et al (1999) (also shown in Table 1). The lobes present a steep SED, consistent with the optically thin synchrotron emission of the jets (Best et al 1999;Laing & Bridle 2013;Nyland et al 2017;Ruffa et al 2019;Grossová et al 2019), while the AGN core SED is flatter, which is consistent with optically thicker (self-absorbed) synchrotron emission (Best et al 1999;Ruffa et al 2019;Grossová et al 2019).…”
Section: Active Galactic Nucleus Continuum Emissionsupporting
confidence: 70%
“…Our results are within the range of spectral indexes found in previous work. The typical spectral index of optically thin synchrotron emission (which corresponds to jets) is in the range of 0.5 α 1.5 in the local Universe (Laing & Bridle 2013;Nyland et al 2017;Ruffa et al 2019;Grossová et al 2019) and 1 α 2 for galaxies at z > 2, with higher values being rarer (Carilli et al 1997;Best et al 1999;Falkendal et al 2019). For the optically thick emission (which corresponds to the core), −0.5 α 0.5 is found in the local Universe (Ruffa et al 2019;Grossová et al 2019) and −1 α 1 is found at z > 2, with most of the measurements being α > 0.5 (Carilli et al 1997;Athreya et al 1997;Best et al 1999;Falkendal et al 2019).…”
Section: Active Galactic Nucleus Continuum Emissionmentioning
confidence: 99%
“…Additionally, another complication with the lower X-ray luminosity systems is that one cannot assume that any undetected X-ray cavities are well traced by the radio lobes, since such systems often host high-power radio sources whose lobes extend far beyond the dense atmospheres (e.g. NGC 4261, IC4296, IC1459, NGC 1600, NGC 5090, UGC11294, ARP308; Diehl & Statler 2008;Sun 2009;Cavagnolo et al 2010;Duţan & Caramete 2015;Kolokythas et al 2018;Ruffa et al 2019;Grossová et al 2019). Table 3 shows that H α filaments are mostly found in groups and ellipticals where the radio emission is filling the X-ray cavities (the exceptions are NGC 499, NGC 410, and NGC 4104, see Table 3).…”
Section: Group and Ellipticals Subsamplementioning
confidence: 99%